Biomaterials in siRNA Delivery: A Comprehensive Review. Issue 21 (4th October 2016) - Ho, William; Zhang, Xue‐Qing; Xu, Xiaoyang
Abstract : With the dearth of effective treatment options for prominent diseases including Ebola and cancer, RNA interference (RNAi), a sequence‐specific mechanism for genetic regulation that can silence nearly any gene, holds the promise of unlimited potential in treating illness ever since its discovery in 1999. Given the large size, unstable tertiary structure in physiological conditions and negative charge of small interfering RNAs (siRNAs), the development of safe and effective delivery vehicles is of critical importance in order to drive the widespread use of RNAi therapeutics into clinical settings. Immense amounts of time and billions of dollars have been devoted into the design of novel and diverse delivery strategies, and there are a handful of delivery systems that have been successfully translated into clinic. This review provides an introduction to the in vivo barriers that need to be addressed by siRNA delivery systems. We also discuss the progress up to the most effective and clinically advanced siRNA delivery systems including liposomal, polymeric and siRNA conjugate delivery systems, as well as their design to overcome the challenges. Abstract : Small interfering RNA (siRNA) therapy holds the potential of treating almost any illness, on the condition that drawbacks in physiological delivery are effectively addressed. A wide range of biomaterials designed to assess these challenges in siRNA delivery are discussed with a focus on significant developments in lipid, polymer and inorganic delivery technologies.